A two-phase hybrid algorithm for the periodic rural postman problem with irregular services on mixed graphs - Benavent, Enrique; Corberán, Ángel; Laganà, Demetrio; Vocaturo, Francesca (European journal of operational research, 2023)
•We focus on the periodic rural postman problem with irregular services.•We propose an algorithm that combines heuristics and mathematical programming.•Multi-start heuristics are used to construct initial solutions.•Some parts of these solutions are recombined through a model-based approach.•The results of an extensive computational study are presented. In this article we address the periodic rural postman problem with irregular services (PRPP–IS), where some arcs and/or edges of a mixed graph must be traversed (to be serviced) a certain number of times in some subsets of days of a given time horizon. The goal is to define a set of minimum cost tours, one for each day or period of the time horizon, that satisfy the service requirements. For this problem we propose a two-phase algorithm that combines heuristics and mathematical programming. In the first phase, two different procedures are used to construct feasible solutions: a multi-start heuristic based on feasibility pump and a multi-start constructive heuristic. From these solutions, some fragments (parts of tours associated with the different days) are extracted. The second phase determines a solution for the PRPP–IS by combining the fragments by means of a mathematical model. We show the effectiveness of this solution approach through an extensive experimental phase on different sets of instances.